2020
DOI: 10.3892/ol.2020.12295
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer cell apoptosis is induced by a proteoglycan extracted from Ganoderma lucidum

Abstract: The Traditional Chinese Medicine, Ganoderma lucidum , has been widely used for its immunity-related and anti-cancer effects. Fudan-Yueyang-Ganoderma lucidum (FYGL) is a proteoglycan, extracted from Ganoderma lucidum , that has shown safe anti-diabetic activity in vivo . The present study demonstrated that FYGL could selectively inhibit the viability of PANC-1 and BxPC-3 pancreatic cancer cells in a dose dependent manner, but not in Mia PaCa-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…In pancreatic cancer, it has been reported that scoparone inhibits tumor progression via PI3K/Akt signaling pathway [ 9 ]. Besides, a proteoglycan extracted from Ganoderma lucidum can induce cancer cell apoptosis [ 10 ]. The prescription of Xiaoji recipe is mainly composed of Curcuma zedoaria (10 g, E Zhu), Polygonum cuspidatum (10 g, Huzhang), clematis root (10 g, Weilingxian), Rhizoma Paridis (10 g, Zhonglou), and Eupolyphaga Steleophaga (10 g, Tubiechong).…”
Section: Introductionmentioning
confidence: 99%
“…In pancreatic cancer, it has been reported that scoparone inhibits tumor progression via PI3K/Akt signaling pathway [ 9 ]. Besides, a proteoglycan extracted from Ganoderma lucidum can induce cancer cell apoptosis [ 10 ]. The prescription of Xiaoji recipe is mainly composed of Curcuma zedoaria (10 g, E Zhu), Polygonum cuspidatum (10 g, Huzhang), clematis root (10 g, Weilingxian), Rhizoma Paridis (10 g, Zhonglou), and Eupolyphaga Steleophaga (10 g, Tubiechong).…”
Section: Introductionmentioning
confidence: 99%
“…A proteoglycan extracted from Ganoderma lucidum known as Fudan-Yueyang-Ganoderma lucidum (FYGL) was found to increase autophagosome levels and prevent autolysosome fusion, indicating late-stage autophagic inhibition effects [ 363 ]. FYGL also reduced Bcl-2 expression and increased cleaved caspase-3 which led to increased ROS and reduced MMP, indicating apoptotic potential [ 363 ]. However, these results were only present in PANC-1 and not MiaPaCa2 cells, suggesting cell type specific effects and require further investigations.…”
Section: Inhibiting Autophagic Machinerymentioning
confidence: 99%
“…Even though their exact mechanism of action is unclear, they seem to converge to a common path of apoptosis inhibition. Fudan-Yueyang-Ganoderma lucidum (FYGL; a proteoglycan extracted from Ganoderma lucidum) and Alantolactone demonstrated inhibitory effect in late-stage of autophagy along with increased apoptotic potential, mediated by elevated ROS production and suppression of STAT3 and Bcl-2 respectively (67)(68)(69)(70). Curcumin is also capable of inducing pro-apoptotic effects, by increasing the BAX/Bcl-2 ratio (71), while ursolic acid (UA) downregulated autophagy, predominantly via inducing cell cycle arrest (72).…”
Section: Targeting Autophagy In Pdacmentioning
confidence: 99%